Literature Review: The Effectiveness of the 5E Learning Cycle Model in Addressing Science Misconceptions among Elementary School Students - Novelina, Fryda; Rahmawati, Yuli; Utami, Nidya Chandra Muji (Universitas Muhammadiyah Surakarta, 2025)
Misconceptions are one of the primary obstacles in learning science at the elementary school level, which can hinder in-depth understanding of concepts and disrupt the learning process, ultimately causing students to fail in their learning. This study aims to examine the role of the 5E Learning Cycle model (Engage, Explore, Explain, Elaborate, Evaluate) in overcoming misconceptions of science concepts among elementary school students through a literature review approach. The method used is a systematic literature review of various relevant scientific sources over the past ten years. The research findings indicate that the 5E Learning Cycle model is effective in identifying, clarifying, and reconstructing students' misconceptions through structured and student- centered learning stages. The